Adherence to allergen immunotherapy improves when patients choose the route of administration: Subcutaneous or sublingual (2015)
ABSTRACT: Background: Immunotherapy has shown to be an effective treatment for the management of some IgE-mediated allergies. However, due to its long duration, a high number of patients withdraw from it before completion. Objective: Explore if allowing patients to select the route of immunotherapy, educational sessions and strict follow-up could improve treatment compliance. Methods: Patients consulting allergy service were divided into two groups; if they chose the route of administration of immunotherapy, they were selected for the active group; if their physician decided, they were selected for the control group. All patients had to attend the allergy service monthly for control. Before the first application of immunotherapy, all patients received an educative session about the benefits and risks of the treatment. Patients in the active group received an additional session about subcutaneous and sublingual routes and they chose the most appropriate according to their personal characteristics. Results: A total of 204 patients were in the active group and 103 were included in the control group. At six months, a total of 46 patients withdrew from immunotherapy during follow-up, 24 (11%) in the active group and 22 (21%) in the control group (p=0.02). In the active group we observed no statistically significant difference in adherence between those who preferred subcutaneous or sublingual immunotherapy; however in the control group, the drop out of sublingual immunotherapy was significantly higher than those who received subcutaneous (p=0.05). Conclusion: Educational sessions, strict follow-up and considering personal preferences of patients could improve adherence to allergen immunotherapy.